SOCIALIZATION OF MANUAL AND ELECTRONIC MEDICAL RECORD SYSTEMS AT PUSKESMAS SEI. NANAM SOLOK REGENCY - Kamal, Syamsul; Mardi, Yuli; Prihatin, Endang (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The use of the Electronic Medical Record System (RME) in health service facilities is a need and demand carried out by health workers, which is related to Permenkes No. 24 of 2022, that RME has been used before December 31, 2023, in all Health Service Facilities. At the Sii Health Center. Nanam Kab. Solok, medical record activities are still carried out manually. The problem is that medical record staff do not understand electronic medical records which will be implemented in health care facilities throughout Indonesia. Once the importance of RME, RME Socialization, and the Manual Medical Record System was carried out at the Sei Health Center. Nanam Kab. Solok on September 22, 2022, there were 12 participants, namely dr, P-Care Health Center, and medical record staff at Sei Health Center. Nanam Kab. Solok and student Apikes Iris. During this socialization, it was explained to participants of the RME system, Manual Medical Record (RMM), Legal Basis for Medical Records, advantages and disadvantages of manual and electronic RME systems, Obstacles and challenges of RME, participants who attended the socialization listened to information with enthusiasm and enthusiasm, in elaborating on this material, some asked questions and discussions who did not understand Manual and Electronic Medical Records. The purpose of this activity is to make the puskesmas staff, especially the medical record department, understand and understand RME and RMM.